Neuropsychological outcomes after epilepsy surgery: A comparison of stereo electroencephalography and subdural electrodes - Arya, Ravindra; Frink, Clayton; Kargol, Christina; Byars, Anna W.; Huddleston, David; Diedenhofer, Donna B.; Aungaroon, Gewalin; Ervin, Brian; Horn, Paul S.; Ihnen, S. K. Z.; Tenney, Jeffrey R.; Kremer, Kelly; et al. (European journal of neurology, 2023)
We analyzed the association of neuropsychological outcomes after epilepsy surgery with the intracranial electrode type (stereo electroencephalography [SEEG] and subdural electrodes [SDE]), and electrical stimulation mapping (ESM) of speech/language. Drug-resistant epilepsy patients who underwent comprehensive neuropsychological evaluation before and 1 year after epilepsy surgery were included. SEEG and SDE subgroups were matched by age, handedness, operated hemisphere, and seizure freedom. Postsurgical neuropsychological outcomes (adjusted for presurgical scores) and reliable change indices were analyzed as functions of electrode type and ESM. Ninety-nine patients aged 6-29 years were included with similar surgical resection/ablation volumes in the SEEG and SDE subgroups. Most of the neuropsychological outcomes were comparable between SEEG and SDE subgroups; however, Working Memory and Processing Speed were significantly improved in the SEEG subgroup. Undergoing language ESM was associated with significant improvements in Spelling, Letter-Word Identification, Vocabulary, Verbal Comprehension, Verbal Learning, and Story Memory scores, but a decline in Calculation scores. Intracranial evaluations with SEEG and SDE are comparable in terms of long-term postsurgical neuropsychological outcomes. Our data suggest that SEEG may be associated with improvements in working memory and processing speed, representing cognitive domains served by spatially distributed networks. Our study also supports wider use of language ESM before epilepsy surgery, preferably using other language tasks in addition to visual naming. Rather than the type of electrode, postsurgical neuropsychological outcomes are driven by whether language ESM was performed or not, with beneficial effects of language mapping.